2020
DOI: 10.1016/j.psychres.2020.113382
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of psychological morbidities among general population, healthcare workers and COVID-19 patients amidst the COVID-19 pandemic: A systematic review and meta-analysis

Abstract: Highlights This is the first review determining psychological morbidities amidst COVID-19 pandemic. Almost half of the general public had a significant mental health impact. Poor sleep quality was the commonest problem followed by stress, psychological distress. The burden was highest among the COVID-19 patients followed by healthcare workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
450
15
21

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 462 publications
(518 citation statements)
references
References 69 publications
32
450
15
21
Order By: Relevance
“…Pregnant and postpartum women also showed obvious higher prevalence rates of mental disorders during the COVID-19 pandemic than the general population. A systematic review and meta-analysis that included 50 studies found that the prevalence rates of anxiety, depression, psychological distress, and poor sleep quality among the general population were 26, 24, 26, and 34%, respectively (Krishnamoorthy et al, 2020). In this meta-analysis, we found that the pooled RRs of anxiety and depression in pregnant women were 1.65 (95% CI: 1.25-2.19) and 1.08 (95% CI: 0.80-1.46), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Pregnant and postpartum women also showed obvious higher prevalence rates of mental disorders during the COVID-19 pandemic than the general population. A systematic review and meta-analysis that included 50 studies found that the prevalence rates of anxiety, depression, psychological distress, and poor sleep quality among the general population were 26, 24, 26, and 34%, respectively (Krishnamoorthy et al, 2020). In this meta-analysis, we found that the pooled RRs of anxiety and depression in pregnant women were 1.65 (95% CI: 1.25-2.19) and 1.08 (95% CI: 0.80-1.46), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Some of them, such as panic disorder, have a higher prevalence during pregnancy than the lifetime prevalence rates for women in the general population [125]. During pandemics, the prevalence of psychological distress and symptoms of mental illness tends to be higher compared to routine periods [126]. A recent systematic review and meta-analysis reported that stress was the most common psychological after-effect among the general population during COVID-19 pandemic.…”
Section: Psycho-social Aspectsmentioning
confidence: 99%
“…A recent systematic review and meta-analysis reported that stress was the most common psychological after-effect among the general population during COVID-19 pandemic. It has been suggested that the reason for such a high burden is the prolonged quarantine [126]. Among the major stressors contributing to worldwide emotional distress and increased risk for psychiatric illness associated with the COVID-19 pandemic, are uncertainty, lack of resources, financial losses, violation of personal liberty, and conflicting messages from authorities [127].…”
Section: Psycho-social Aspectsmentioning
confidence: 99%
“…Emerging studies have documented the negative effects of working at the frontline in health and social care during COVID-19. To date, the vast majority of these have been conducted in China [ 5 ], where the virus is thought to have originated. For example, Lai et al [ 6 ] examined the mental health of 1257 staff in 34 hospitals in China and found large proportions reported symptoms of depression (50.4%), anxiety (44.6%), insomnia (34.0%) and distress (71.5%).…”
Section: Introductionmentioning
confidence: 99%